2022
DOI: 10.3390/ph15010091
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-XL but Not Bcl-2 Is a Potential Target in Medulloblastoma Therapy

Abstract: Medulloblastoma (MB) is the most common solid tumour in children and, despite current treatment with a rather aggressive combination therapy, accounts for 10% of all deaths associated with paediatric cancer. Breaking the tumour cells’ intrinsic resistance to therapy-induced cell death should lead to less aggressive and more effective treatment options. In other tumour entities, this has been achieved by modulating the balance between the various pro- and anti-apoptotic members of the Bcl-2 family with small mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…We characterized the sensitivity of two representative GSC-ECLs (G03 and G09) towards treatments with ABT-263 and WEHI-539 by dose-dependent experiments, both with and without TMZ (Supplementary Fig. S3 ) Based on this and on bibliography 28 , 30 33 , we selected a concentration of 1 μM for both inhibitors. In response to single treatments with these BH3-mimetics, G01, G03, G08, and G09 cell lines underwent a significant increase in cell death (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We characterized the sensitivity of two representative GSC-ECLs (G03 and G09) towards treatments with ABT-263 and WEHI-539 by dose-dependent experiments, both with and without TMZ (Supplementary Fig. S3 ) Based on this and on bibliography 28 , 30 33 , we selected a concentration of 1 μM for both inhibitors. In response to single treatments with these BH3-mimetics, G01, G03, G08, and G09 cell lines underwent a significant increase in cell death (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to note that knockdown of BCL-XL alone did not induce a significant reduction of viable cells in our data. Previously published data describes an apoptosis sensitizing effect of BCL-XL inhibition in MYC -amplified MB cell lines when additionally treated with apoptosis inducing chemotherapeutic agents such as doxorubicin [ 49 ]. This suggests that part of the observed synergistic cytotoxicity of class I HDACi and BCL-XLi may be caused by the additional apoptosis inducing effect of class I HDACi.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-apoptotic BCL-2 proteins are commonly highly expressed in cancer and are readily targetable by a suite of BH3 mimetics [ 49 ]. In this regard, a small number of studies previously suggested BCL-XL as a potential target in medulloblastoma [ 50 52 ]. Using BH3 profiling and dynamic BH3 profiling following cisplatin treatment, we identified BCL-XL as the dominant anti-apoptotic dependency, while cisplatin with WEHI-539 had a synergistic effect on cell viability.…”
Section: Discussionmentioning
confidence: 99%